Vitales, D., Nieto Feliner, G., Vallès, J., Garnatje, T., Fırat, M. & Álvarez, I. (2018) A new circumscription of the Mediterranean genus Anacyclus (Anthemideae, Asteraceae) based on plastid and nuclear DNA markers. Phytotaxa 349 (1): 1–17. - Vitales, Daniel; Feliner, Gonzalo Nieto; Vallès, Joan; Garnatje, Teresa; Firat, Mehmet; Álvarez, Inés (Phytotaxa, 2018)
N/A